Family-focused practices in addictions: a scoping review protocol. Issue 1 (13th January 2018) - Kourgiantakis, Toula; Ashcroft, Rachelle
Abstract : Introduction: Families are significantly impacted by addictions and family involvement in treatment can reduce the harms and can also improve treatment entry, treatment completion and treatment outcomes for the individual coping with an addiction. Although the benefits of family-focused practices in addictions have been documented, services continue to have an individual focus and research on this topic is also limited. The objective of this study is to map the extent, range and nature of evidence available examining family interventions in addictions and identify gaps to guide future research, policy and practice. Methods and analysis: This is a scoping review using the five-stage framework developed by Arksey and O'Malley. We will include published and unpublished empirical studies focusing on any type of family interventions in addiction treatment between 2000 and the present in English or French. A reviewer will search for literature that meets the inclusion criteria through the following electronic databases: MEDLINE, PsycINFO and Social Services Abstracts. For a comprehensive search, we will also hand-search reference lists, web sites and key journals. Data will be charted and sorted using a thematic analysis approach. Ethics and dissemination: This review will be the first to examine all forms of family-focused practices for both substance use and problem gambling treatment for adults. It will provide information about existing service provisions and gaps in practice. This review can be used to start moving towards the development of best practices for families in addiction treatment. The results will be disseminated through a peer-reviewed journal and at mental health and addiction conferences.